Analisis Semantik Gramatikal pada Lirik Lagu Everything You Are Karya Hindia - Juan Pius Pratomo (Universitas Islam Sumatera Utara, 2026)
The rapid expansion of modern music, particularly through both paid and free streaming platforms, has intensified scholarly interest in song lyrics as not merely entertainment but as complex linguistic artifacts embedded with semantic and contextual meanings. This study addresses the problem of how grammatical structures contribute to meaning construction in song lyrics, focusing on the question of how grammatical forms shape semantic interpretation in Hindia’s “Everything You Are.” Employing a qualitative descriptive approach grounded in Abdul Chaer’s grammatical theory (2013), data were collected through attentive listening and systematic note-taking of linguistic units, including words, phrases, and clauses. The data were subsequently classified into three primary morphological processes: affixation, reduplication, and composition. The findings reveal 13 distinct grammatical forms that demonstrate a rich interplay between structure and meaning, highlighting how grammatical processes function to intensify emotional nuance and ideological expression. The analysis shows that these linguistic features reinforce central themes of self-acceptance, unconditional love, and human existence. This study argues that grammatical-semantic analysis of song lyrics provides deeper insights into how language constructs meaning within socio-cultural contexts, positioning song lyrics as significant objects of linguistic inquiry.